The Effect of Attitudes, Interests, and Motivation Students on Text-Type Materials in Yogyakarta Elementary School - Huda, Noor Auliya; Dewanti, Sintha Sih (Mimbar Sekolah Dasar, 2025)
Understanding the types of texts is an important aspect in strengthening the basic literacy of elementary school students, especially in Indonesian subjects. However, low affective readiness such as attitude, interest, and motivation to learn is often an obstacle in achieving optimal learning outcomes. This study aims to examine the influence of attitudes, interests, and learning motivation on the understanding of text type materials in grade IV and V students in one of the State Elementary Schools in Yogyakarta. The sample in this study amounted to 30 students who were taken using the saturated sample technique. This study uses a quantitative approach with correlational methods and multiple regression analysis. The instruments used were a questionnaire on the scale of attitudes, interests, and motivations, as well as a test of understanding the type of text. The results showed that simultaneously, three independent variables (attitude, interest, and motivation) had a significant influence on the understanding of the type of text, which was indicated by an R Square value of 0.964. However, only a fraction of the attitude and motivation variables showed a significant influence, while interest was not statistically significant. These results show that affective factors, especially attitudes and motivations, play an important role in supporting students' understanding of different types of texts. This research provides important implications in the development of Indonesian learning strategies that are more contextual and oriented to student character.